Digital Literacy & Digital Skills Scenario of ASEAN Marginal Workers during COVID-19 - Kamolrat Intaratat (New Innovations in Economics, Business and Management Vol. 10, 2022)
The goal of this study is to look at the scenario of workforces relevant to digital literacy and digital skills among marginal workers in six ASEAN countries; the scenario of digital literacy and digital skills relevant to current and future job skills among all marginal workers; and the government’s policy to support any digital reskilling and upskilling among workforces, including marginal workers, in order to serve well with all demanding skills. Based on their similar digital literacy and digital skills workforces background, the qualitative research included document study and e-interviews with 178 key informants from all relevant stakeholders: policy, private sector, and marginal workers. The method employed was narrative description. The following are the findings:1) The scenario of workforces relevant to digital literacy and digital skills among all marginal workers from the selected ASEAN countries affected by COVID-19, as well as technological disruption, contributed in a pattern of businesses shifting from the formal to the informal sector, with the low skilled being the most affected. The majority of online white-collar workers believe in the future of employment. 2) The major emerging jobs in the scenario of digital literacy and digital skills relevant to current and future jobs are data analysts and data scientists, digital marketing specialist, software and application developer, as well as some soft skills: creative and analytical thinking, problem-solving, and so on. Administrative jobs such as secretaries, accounting, clerking, and human resources would be in decline. 3) The government’s policy to assist workforce reskilling and upskilling for future jobs has been found to be similar across ASEAN: a) accelerate all relevant digital competency by partnering with private and industry sectors through the TVET training system; and b) work with industries to revamp national curriculums via digital learning pathways and emerging skillsets. The PPP strategy should be used to transfer knowledge and create a digital ecosystem.